PERAN KEBIJAKAN MEKANISASI DALAM TRANSFORMASI PERTANIAN TRADISIONAL KE PERTANIAN MODERN DI INDONESIA - Fitri, Annisa; Agustia, Devi; Wahyuni, Ari; Andriyanty, Reny; Karmaita, Yummama (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
Agriculture in Indonesia still largely relies on traditional methods that are inefficient and result in low productivity. In the face of global challenges such as climate change, food crises, and market competition, the shift toward a modern agricultural system has become a necessity. One important step in this process is the implementation of agricultural mechanization supported by government policy. This study uses the Systematic Literature Review (SLR) method to examine the role of mechanization policy in accelerating the transformation of agriculture in Indonesia. The findings show that the success of mechanization policy is not solely determined by the provision of agricultural tools and machinery, but also by the social and economic readiness of farmers, the strength of local institutions, human resource training, and the sustainability of government support. Policies that focus only on technical aspects and are implemented unilaterally risk causing unequal access to technology and low adoption rates among small-scale farmers. Therefore, mechanization policies must be designed comprehensively, involve multiple stakeholders, and be adapted to real conditions in the field to achieve agriculture that is fair, resilient, and sustainable.